Earning Management and Firm Value: A Systematic Literature Review - Ade Sintya Lindora (PT. Hafasy Dwi Nawasena, 2026)
This study is about the idea of Earnings Management and Firm Value in accounting. It looks at how these ideasre connected and how they have changed over time. The study used a method called Systematic Literature Review, which's a way of carefully looking at lots of research papers. This study chose 10 research papers that were published between 2021 and 2026 from well-known places like Scopus, Web of Science and Emerald. The results of the study show that when companies do Earnings Management in a way that is not honest it can hurt the value of the company. This is because it makes it harder for people to know what is really going on with the company and it can also make the people in charge of the company do things that're not good for the company. If This study says that it is very important for companies to be honest about their finances and to have rules in place. Researchers should keep studying Earnings Management and look at new ways to detect it like using artificial intelligence. Earnings Management is a deal and companies need to be careful, about it. Earnings Management can hurt Firm Value so companies should try to avoid it. The study of Earnings Management and Firm Value is important. Will keep being studied in the future.